Visual and ultrasensitive detection of mercury ions based on urease catalysis and responsive photonic crystals. (November 2021) - Li, Lu; Dong, Xugang; Liu, Zhanfang; Wei, Juan; Li, Jingru; Zhou, Hong; Zhu, Jun; Shi, Xinwei
Abstract: In this study, a visual and ultrasensitive method for the determination of trace mercury ions in water was developed based on the high efficiency of urease catalysis and pH-sensitive inverse opal polymeric photonic crystals (IOPPCs). Mercury ions can inhibit urea hydrolysis and suppress the production of ammonium and bicarbonate ions in the solution, resulting in the redshift of IOPPCs. Therefore, the redshift of IOPPCs Bragg diffraction is directly related to the concentration of mercury ions. Meanwhile, the color of IOPPCs varied significantly with the shift of the Bragg diffraction wavelength, thus achieving the visual semi-quantitative detection of mercury ions by the naked eye. The minimum detection concentration of this method is 5 × 10 −16  g/L, which is much lower than the maximum contaminant level for the safe drinking of water (2 × 10 −6  g/L) recommended by the environmental protection agency (EPA), USA. In addition, this is a simple and quick method for effective on-site detection of mercury ions, which shows a great promise in emergency leakage monitoring and control. Graphical abstract: Image 1 Highlights: A simple and visual method for detection of mercury ions was developed. The detection limit can be as low as 5 × 10 −16  g/L. This method has good selectivity, interference immunity and reusability.